Pelaksanaan Pembelajaran Seni Budaya di SMP Negeri 23 Kerinci - Ingria Nada Contesi; Marzam Marzam (SENDRATASIK UNP, 2022)
The purpose of this study was to describe the implementation of cultural arts learning with the material of Traditional Musical Instrument Playing Techniques at SMP Negeri 23 Kerinci. This type of research is a qualitative research with descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques were carried out by means of observation, interviews, and literature studies. The steps of analyzing the data, Describing, and Inferring. The results of the study indicate that the implementation of cultural arts learning with the material of Traditional Musical Instrument Playing Techniques at SMP NEGERI 23 Kerinci has not gone well. This is due to: (1) Teachers do not have angklung musical instruments which are being used as material for cultural arts subjects. This makes teachers take shortcuts by using a keyboard (orgen) instead of the traditional angklung musical instrument. (2) Some students still practice playing traditional musical instruments that are not in accordance with the indicators or in other words carelessly when playing traditional musical instruments. The results of the evaluation of learning techniques for playing traditional musical instruments, the highest score is 90 and the lowest value is 75.